2008
DOI: 10.1002/jssc.200800212
|View full text |Cite
|
Sign up to set email alerts
|

Separation and HPLC analysis of 15 benzodiazepines in human plasma

Abstract: Benzodiazepines (BZDs) are often prescribed to schizophrenic or depressed patients, as a part of polypharmacy regimens. An HPLC method has been developed for the simultaneous determination of 15 BZDs in human plasma. Separation was obtained by using a C8 RP column and a mobile phase composed of 65% aqueous phosphate buffer at pH 3.0 and 35% ACN. The UV detector was set at 220 nm and clomipramine was used as the internal standard. A careful pretreatment procedure of plasma samples was developed, using SPE with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…2,7,14,15 The first column tested was Zorbax SB-C8 packed with an endcapped octyl-silica gel stationary phase. The most suitable mobile phase composition found in isocratic elution mode was ACN/deionised water with acetic acid, pH 3.0, 30/70 (v/v).…”
Section: Optimization Of the Chromatographic Separation Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…2,7,14,15 The first column tested was Zorbax SB-C8 packed with an endcapped octyl-silica gel stationary phase. The most suitable mobile phase composition found in isocratic elution mode was ACN/deionised water with acetic acid, pH 3.0, 30/70 (v/v).…”
Section: Optimization Of the Chromatographic Separation Conditionsmentioning
confidence: 99%
“…3,4 Many studies on these drugs can be found in the literature. [5][6][7][8] Diverse analytical methods for determination of benzodiazepines in various matrices have been published, 9,10 e.g. potentiometry, 11 immunoassays, 12 spectrophotometry 13 and also separation techniques that represent a clear majority of the reported methods because they allow determination of individual compounds in often rather complicated mixtures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liquid chromatography has become an important tool for routine determination of BZD owing to its specificity, rapidity and sensitivity [4][5][6][7][8]. Although high-performance liquid chromatography (HPLC) with mass spectrometry detection [5][6][7] is highly selective, the cost of the instrumentation makes it less suitable for clinical or toxicology laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…Although high-performance liquid chromatography (HPLC) with mass spectrometry detection [5][6][7] is highly selective, the cost of the instrumentation makes it less suitable for clinical or toxicology laboratories. In contrast, HPLC-UV detection or diode array detection (DAD) instrumentation is widely available in most analytical laboratories [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%